2011
DOI: 10.1007/s10900-011-9447-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer in India: An Epidemiologic and Clinical Review

Abstract: Oral cancer is one of the most fatal health problems faced by the mankind today. In India, because of cultural, ethnic, geographic factors and the popularity of addictive habits, the frequency of oral cancer is high. It ranks number one in terms of incidence among men and third among women. Several factors like tobacco and tobacco related products, alcohol, genetic predisposition and hormonal factors are suspected as possible causative factors. Hence the study was designed to determine the prevalence of Oral C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 8 publications
1
59
1
3
Order By: Relevance
“…A national cancer mortality through nationally representative survey (Dikshit et al, 2012) revealed oral (lip and pharynx) cancer to be the most leading cause of death amongst males in the age group of 30-69 years. Byakodi et al (2012) have lately reported an overall prevalence of oral cancer to the tune of 1.12% amongst all the outpatients attending a dental hospital at Sangli Maharashtra.…”
Section: Cancer Mouthmentioning
confidence: 99%
See 1 more Smart Citation
“…A national cancer mortality through nationally representative survey (Dikshit et al, 2012) revealed oral (lip and pharynx) cancer to be the most leading cause of death amongst males in the age group of 30-69 years. Byakodi et al (2012) have lately reported an overall prevalence of oral cancer to the tune of 1.12% amongst all the outpatients attending a dental hospital at Sangli Maharashtra.…”
Section: Cancer Mouthmentioning
confidence: 99%
“…These cancer related myths can only be overcome by better education. Byakodi et al (2012) from a big city (Banglore) of India further stressed that education about ill effects of tobacco and alcohol consumption is necessary at a broader scale…”
Section: Cancer Mouthmentioning
confidence: 99%
“…As many as 75 percent of oral cancers are linked to modifiable behaviors such as tobacco use, chewing betel, 'paan' and excessive alcohol consumption. 3 The popularity of addictive habits along with cultural, ethnic and geographic factors have all played a vital role in the high incidence of oral carcinoma in India. In many Asian cultures chewing betel, paan, and areca is known to be a strong risk factor for developing oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Oral cancers are one of the commonest cancers and ranks number one in terms of incidence among men and third among women [1]. In the west, cancer of the tongue and the floor of the mouth are common, whereas in the Indian subcontinent, the cancers of gingival and buccal mucosa are common due to placement of tobacco quid in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%